Selection of an ACE inhibitor in clinical practice - OD Ostroumova; ML Maksimov; OV Dralova; AS Yermolayeva (Медицинский совет, 2014)
Currently, ACE inhibitors are considered to be the gold standard in the treatment of cardiovascular diseases. They all have cardio-, vaso- and nephroprotective and positive metabolic effects; however, despite the large number of the so-called class effects, the drugs differ in pharmacokinetic characteristics which determine the difference in their clinical effects. The article is about choosing the optimal drug from the group of ACE inhibitors in clinical practice.